Immunomodulation with self-crosslinked polyelectrolyte multilayer-based coatings - Knopf-Marques, Helena; Singh, Sonali; Htwe, Su Su; Wolfova, Lucie; Buffa, Radovan; Bacharouche, Jalal; Francius, Grégory; Voegel, Jean-Claude; Schaaf, Pierre; Ghaemmaghami, Amir M.; Vrana, Nihal E.; Lavalle, Philippe (American Chemical Society, 2016)
This study aims to design an optimal polyelectrolyte multilayer film of poly-L-lysine (PLL) and hyaluronic acid(HA) as an anti-inflammatory cytokine release system in order to decrease the implant failure due to any immune reactions. The chemical modification of the HA with aldehyde moieties allows self-cross-linking of the film and an improvement in the mechanical properties of the film. The cross-linking of the film and the release of immunomodulatory cytokine (IL-4) stimulate the differentiation of primary human monocytes seeded on the films into pro-healing macrophages phenotype. This induces the production of antiinflammatory cytokines (IL1-RA and CCL18) and the decrease of proinflammatory cytokines secreted (IL-12, TNF-α, and IL-1β). Moreover, we demonstrate that cross-linking PLL/HA film using HA-aldehyde is already effective by itself to limit inflammatory processes. Finally, this functionalized self-cross-linked PLL/HA-aldehyde films constitutes an innovative and efficient candidate for immunomodulation of any kind of implants of various architecture and properties.